Introduction to chemical processes : - Murphy, Regina M. (McGraw Hill, 2007)
Introduction to Chemical Processes: Principles, Analysis, Synthesis" enhances student understanding of the connection between the chemistry and the process. Users will find strong coverage of chemistry, gain a solid understanding of what chemical processes do (convert raw materials into useful products using energy and other resources), and learn about the ways in which chemical engineers make decisions and balance constraints to come up with new processes and products. The author presents material and energy balances as tools to achieve a real goal: workable, economical, and safe chemical processes and products. Loaded with intriguing pedagogy, this text is essential to a students first course in Chemical Engineering. Additional resources intended to guide users are also available as package options, including the Engineering Equation Solver (EES) software, ChemSkill Builder and the well-known "Perry's Chemical Engineering Handbook".